The COVID-19 pandemic and the future of the prison - Maruna, Shadd (Crime and justice, 2022)
Since the discovery of the “jail disease,” probably typhus, in the eighteenth century, health experts have recognized that the prison is a near perfect incubator of contagious disease. Early in the COVID-19 pandemic, therefore, public health authorities and human rights groups advocated immediate and sustained decarceration of overcrowded prisons to save lives and stop the spread of the virus. Yet, decarceration efforts globally were uneven and largely failed to live up to expectations. Instead, prison systems typically sought to control the spread of COVID-19 by imposing strict “lockdowns” on prisoner movement that bordered on long-term solitary confinement in many jurisdictions. The consequences of these severe conditions on prisoners’ mental and physical health are only just emerging. The ramifications for future prison reform efforts may be more profound. If a deadly pandemic is not enough to instigate a reimagining of the role of prison in society, it is unclear what could.